Touchpoint : an interactive authoring tool for creating multimedia android documents - Padmini Nair, Sugendran Nair (Universiti Malaysia Sarawak (UNIMAS), 2014)
There are many mobile applications found in market that aid in documenting and providing information to users in a quick and simple manner. Information is not only limited to youngsters but also should reach the elderly group as well. To deliver information in a manner whereby it would be easy for the elderly to understand is challenging. In addition, the authors of documents for the mobile might face difficulties to create such applications without the aid of authoring tool as it requires technical skills to do so. In order to deliver essential information in an appropriate way to be understood by the elderly, TouchPoint 2. O an authoring tool application has been developed to enable authors to create multimedia documents without requiring any technical skills. Thus, the output of the application is targeted at TouchPoint Readers to ensure that the information is reachable t .... o them via the predesigned templates consisting of multimedia components such as text, audio, video and image. The incorporated integrated multimedia component is used to provide information via multimodal communication approach to the elderly. Moreover, providing interactive features has been expected to enable authors to control the flow and content of the document easily. The significance of TouchPoint 2. 0 application would be to allow the authors to create their very own multimedia documents as well as to benefit the elderly age group.